Development of University Teachers’ Professional Vision of Students’ Prior Knowledge During a Short Pedagogical Training - Södervik Ilona; Vilppu Henna; Boshuizen Henny; Murtonen Mari (International Society for Exploring Teaching and Learning, 2022)
To support university students’ learning, teaching should build on students’ prior knowledge. Therefore, teachers need skills to pay attention to students’ knowledge in teaching-learning situations. Teachers’ underlying conceptual knowledge affects the way they see and interpret situations in classrooms, which is called professional vision. This study examined university teachers’ (N = 53 from different faculties, current and future faculty) professional vision and misconceptions from the perspective of the role of prior knowledge in learning, when watching and interpreting short videos of teaching-learning situations at the start of and after a short pedagogical training. Additionally, participants’ conceptions, beliefs, and approaches to teaching and learning were investigated with a questionnaire. The results show that before the training, there were differences between the teachers from different faculties, but after the training all the teachers scored better in their professional vision concerning prior knowledge. Prospective teachers’ professional vision developed even more than those of current faculty. Furthermore, more developed professional vision was related to more constructivist beliefs of learning. The results show that even short pedagogical interventions can improve teachers’ pedagogical vision. Pedagogical implications of the results are discussed.